2021
DOI: 10.1111/jch.14153
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of topiroxostat and febuxostat on arterial properties in hypertensive patients with hyperuricemia

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
(104 reference statements)
1
22
0
Order By: Relevance
“…A significant reduction in systolic and diastolic BP was reported in a comprehensive meta-analysis of 10 prospective and retrospective studies involving 738 patients 85 treated with allopurinol with a substantial homogeneity across the studies despite a remarkable difference in the characteristics of the study populations. The effects of ULT on BP control is apparently more evident with drugs showing a greater inhibition of XOR activity 86 again supporting its possible involvement in the mechanism of BP increase in patients with hyperuricemia.…”
Section: Treatment Of Hyperuricemia and Hypertensionmentioning
confidence: 72%
“…A significant reduction in systolic and diastolic BP was reported in a comprehensive meta-analysis of 10 prospective and retrospective studies involving 738 patients 85 treated with allopurinol with a substantial homogeneity across the studies despite a remarkable difference in the characteristics of the study populations. The effects of ULT on BP control is apparently more evident with drugs showing a greater inhibition of XOR activity 86 again supporting its possible involvement in the mechanism of BP increase in patients with hyperuricemia.…”
Section: Treatment Of Hyperuricemia and Hypertensionmentioning
confidence: 72%
“…24 Epidemiologically, levels of uric acid and XOR have been reported to be independent risks factor for hypertension. 6,[32][33][34][35][36] The presence of elevated serum uric acid levels has also been reported to be associated with the risk of cardiovascular events in patients with hypertension, even when blood pressure is well controlled. 37 In addition, treatment with the XOR inhibitor topiroxostat in hypertensive patients with hyperuricemia has been shown to improve the urine albumin-to-creatinine ratio (UACR) and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism of this association has not been fully elucidated, several factors related to NAFLD/NASH, including insulin resistance, dietary intake, altered lipid metabolism, the gut microbiome, and the proinflammatory state, are considered to play roles in the pathogenesis of atherosclerosis (36)(37)(38). Supporting the clinical evidence mentioned above, NASH mice fed CDAHFD exhibited significantly augmented neointimal proliferation induced by carotid artery ligation (P < 0.001).Topiroxostat is reported to inhibit plasma XOR activity more effectively than other XOR inhibitors, allopurinol and febuxostat, in both mice (39) and humans (40). Furthermore, XOR inhibition by topiroxostat reversed both increased plasma XOR activity and the progression of neointima formation in NASH model mice of the present study to similar levels observed in control mice independent of liver dysfunction (Figure 4, E and F).…”
Section: Discussionmentioning
confidence: 72%